Smartphone-Powered Electrochemical Biosensing Dongle for Emerging Medical IoT Application - Vaddi Sesha Sai Sandeep, Dr. A. Deepak (International Journal of Advanced Science and Technology, 2020)
In this current scenario people don’t even have time to take care of their own health because they are busy with business. Now a day each and every people have Smartphone. Medical IoT commonly called as healthcare IoT which refers number of IoT devices uses in the healthcare field. This provides wide range of Iot application and the device is particularly designed for the healthcare needs. Here smart phone also plays an important role. A Smartphone is a cellular telephone with integrated computer. So here implement a new technology to maintain their health of the person properly using a device called dongle with their Smartphone, because we can’t see anyone without a Smartphone in this trendy world. Here in this proposed system we can accesses our health level with a device called dongle connected to the Smartphone. Dongle is a device which helps to detect the content of uric acid and glucose level in the blood. The Dongle is a device which can be connected to the mobile phone to see the blood glucose level. The dongle has a disposable strip in the other end it can be connected to the mobile phone. With the help of internet access of 5G data in the Smartphone the glucose level and the uric acid content in the blood level can be detected. The data is collected and then after processing if the glucose level or the uric acid content is abnormal automatically the message is sent to the doctor and then if there is any need for they consultancy the doctor can give the consultation through online.